The Effect of Corticosteroid Administration on Maternal Outcomes in Patients with Hellp Syndrome - Yulistiani Yulistiani; Rana Rana (Green Publisher Indonesia, 2024)
HELLP syndrome is a hemolysis syndrome with microangiopathic blood smears, increased liver enzymes, and low platelets in pregnant and postpartum patients. HELLP syndrome may be a complication or progression of severe preeclampsia. The death rate due to HELLP syndrome is relatively high. The use of corticosteroids is expected to increase platelet counts, reduce LDH values, and reduce liver function parameters to speed up the duration of healing and reduce mortality. Corticosteroids inhibit endothelial activation, reduce vascular endothelial injury, increase hepatic blood flow, prevent thrombotic microvascular hemolysis, and reduce platelet consumption. Objective: To evaluate the effectiveness of corticosteroids in patients with HELLP syndrome. Method: This research was conducted using a literature review method by searching articles from Google Scholar, PubMed, and Science Direct. Results: Administration of corticosteroids can increase platelet counts, reduce AST/ALT values, and reduce the need for blood product transfusions. Conclusion: Corticosteroids effectively increase platelet counts in patients with HELLP syndrome.